2023
DOI: 10.1186/s12902-023-01518-9
|View full text |Cite|
|
Sign up to set email alerts
|

The association between creatinine to body weight ratio and the risk of progression to diabetes from pre-diabetes: a 5-year cohort study in Chinese adults

Tong Li,
Changchun Cao,
Xuan Xuan
et al.

Abstract: Objective Evidence on the association between the creatinine to body weight (Cre/BW) ratio and the risk of pre-diabetes to diabetes development remains limited. Our study aimed to examine the association between the Cre/BW ratio and incident diabetes in pre-diabetic patients. Methods This retrospective cohort study included 24,506 pre-diabetic participants who underwent health checks from 2010 to 2016 in China. We used the Cox proportional-hazards … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Following publication of the original article [ 1 ], the authors reported that the funding information was mistakenly missing in the article.…”
mentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors reported that the funding information was mistakenly missing in the article.…”
mentioning
confidence: 99%